Cardiovascular Imaging by Ultrasound - Hanrath, Peter; Uebis, Rainer; Krebs, Winfried (Developments in Cardiovascular Medicine, 1993)
An international meeting of experts on Cardiovascular Imaging by Ultrasound was held in Aachen from 26-27 April, 1991. It provided new and interesting insights into what has already been achieved in ultrasound-based cardiovascular diagnosis and therapy and what will be introduced in clinical practice in the near future. Since the introduction of ultrasound in clinical practice in 1984 there has been no other physical principle that has added and will continue to add so much to clinical diagnosis and therapy. Echocardiography, once established as a non-invasive diagnostic tool, is increasingly becoming an invasive technique for cardiovascular imaging. This book contains the edited contributions from 38 scientists and engineers from all over the world who presented the most up-to-date findings on 2-dimensional echocardiography, different Doppler modalities, contrast and stress echocardiography and the different modalities of transesophageal echocardiography, including mono-, bi- and multiplane TEE, as well as pulsed and CW-Doppler application via TEE. Exciting and promising developments are discussed in the field of intravascular ultrasound, tissue characterization, ultrasound ablation, ultrasound-based 3-dimensional reconstruction of the heart, and high frequency Doppler analysis